MANAGEMENT OF PHARMACY CHAIN ON THE BASIS OF OUTSOURCING - I. A. Dzhuparova (Фармация и фармакология (Пятигорск), 2015)
The article studies the problems of development of methods of the outsourcing reasoning of a certain business process of pharmacy chains considering the risk on the basis of the system analysis, expert survey, theory of probability, mathematical statistics. Business processes of the pharmacy chain for outsourcing have been indicated. We have offered an “index of outsourcing reasonability” for qualitative evaluation of business processes implementation.